2008
DOI: 10.1051/0004-6361:20078837
|View full text |Cite
|
Sign up to set email alerts
|

NLTE determination of the aluminium abundance in a homogeneous sample of extremely metal-poor stars

Abstract: Aims. Aluminium is a key element to constrain the models of the chemical enrichment and the yields of the first supernovae. But obtaining precise Al abundances in extremely metal-poor (EMP) stars requires that the non-LTE effects be carefully taken into account. Methods. The NLTE profiles of the blue resonance aluminium lines have been computed in a sample of 53 extremely metal-poor stars with a modified version of the program MULTI applied to an atomic model of the Al atom with 78 levels of Al I and 13 levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
164
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 35 publications
16
164
0
Order By: Relevance
“…Just as in the analysis of sodium, only the resonance lines of aluminum can be detected at low metallicities, and they are affected by NLTE effects. Andrievsky et al (2008) calculated NLTE corrections for Al in giants, but for temperatures above 4700 K, implying an extrapolation by up to almost 500 K for some of our stars. Furthermore while they mentioned the dependence of the NLTE corrections on line strength, unfortunately they did not give explicit values.…”
Section: Nlte Effectsmentioning
confidence: 82%
See 1 more Smart Citation
“…Just as in the analysis of sodium, only the resonance lines of aluminum can be detected at low metallicities, and they are affected by NLTE effects. Andrievsky et al (2008) calculated NLTE corrections for Al in giants, but for temperatures above 4700 K, implying an extrapolation by up to almost 500 K for some of our stars. Furthermore while they mentioned the dependence of the NLTE corrections on line strength, unfortunately they did not give explicit values.…”
Section: Nlte Effectsmentioning
confidence: 82%
“…In metal-rich environments however, with a sufficient amount of neutron rich elements that might act as neutron donors, the yields of Al and Na depend on the neutron excess and their abundances are expected to be metallicity dependent (Woosley & Weaver 1995;Gehren et al 2006). Andrievsky et al (2007Andrievsky et al ( , 2008 found constant [Na/Fe] and [Al/Fe] values of −0.21 ± 0.13 and −0.06 ± 0.10, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We did not apply NLTE corrections to our abundances, because the used doublet should be relatively free from NLTE effects (Gehren et al 2004;Andrievsky et al 2008). It is interesting to recall here that both Johnson & Pilachowski (2010) and Marino et al (2011) found a tendency, for stars richer than [Fe/H] −1.0 dex, to exhibit no (anti-)correlation among the usual elements (Na, Al, Mg, C, N, and O).…”
Section: Anti-correlationsmentioning
confidence: 87%
“…Upper limits are treated as detections for the second generation averages for Al (two stars) and O (one star) when computing the mean and standard deviation. The literature data for halo field stars are assembled as follows; bullets represent Gehren et al (2006), star symbols represent Andrievsky et al (2007Andrievsky et al ( , 2008Andrievsky et al ( , 2010, open triangles Cayrel et al (2004), and open diamonds Nissen et al (2002).…”
Section: O Na Mg and Almentioning
confidence: 99%